STATIONARY\MOBILE SEEDS EXTRACTOR FROM FRUITS OF CUCURBIT CROPS - P. N. Tokarev; A. I. Voinov; N. S. Tsiganok (Овощи России, 2015)
The technical specifications and test data in 2012-2014 of a new fixed-mobile seed extractor of pumpkin and squash seeds (varieties of different ripeness, size and shape of fruit and seeds) are presented.